Ecology of Near-Earth Space - Nikoghosyan, E. H.
The technical achievements of our civilization are accompanied by certain negative consequences affect the near-Earth space. The problem of clogging of near-Earth space by "space debris" as purely theoretical arose essentially as soon as the first artificial satellite in 1957 was launched. Since then, the rate of exploitation of outer space has increased very rapidly. As a result, the problem of clogging of near-Earth space ceased to be only theoretical and transformed into practical. Presently, anthropogenic factors of the development of near-Earth space are divided into several categories: mechanical, chemical, radioactive and electromagnetic pollution.
Keywords: Space Sciences